Factors affecting the change of travel channels to Chiang Mai Province during the COVID-19 situation - Aree, Apisara; Nimanussornkul, Kunsuda; Chittsamart, Boonruam (Journal of Medical and Public Health Region 4, 2023)
The purpose of this research was to study factors affecting the travel behaviors of visitors to Chiang Mai. The population was chosen based on the inclusion criteria of 400 people. The data was collected using an online questionnaire between May and September 2022, with Logistic regression analysis. The study found that if the visitors were older, there would be less opportunity to change their travel behaviors. If the traveler was a local single, widowed, or divorced with a planned trip and did not travel during weekends, they will be less likely to change travel behaviors than those with marital status who travel without a planned trip and travel during weekends. The suggestions should be evaluated and studied in other tourist cities in Thailand affected by COVID-19 or other diseases that may have a similar impact, such as Legionnaires’ disease or new emerging diseases that may occur in the future, by studying them periodically as they will impact the main income from travel behavior so that their process could be improved and establishing public health policies that could both satisfy and secure travelers from COVID-19.